Low Dietary Fish Meal Induced Endoplasmic Reticulum Stress and Impaired Phospholipids Metabolism in Juvenile Pacific White Shrimp, Litopenaeus vannamei - Xie, Shiwei; Liu, Yongjian; Tian, Lixia; Niu, Jin; Tan, Beiping (Frontiers in Physiology, 2020)
An 8-week feeding trial was conducted to evaluate the low dietary fish-meal (FM) on growth performance, immune competence and metabolomics response of juvenile Pacific white shrimp, Litopenaeus vannamei reared at low salinity (7‰). Five experimental diets were formulated to contain graded levels (25, 20, 15, 10 and 5%) of FM. Weight gain and survival were decreased with the decreasing FM levels. When dietary FM decreased, glucose, cholesterol, total bile acids and triglyceride in hemolymph decreased. Fatty acid synthesis was promoted and fatty acid lipolysis was reduced in hepatopancreas of shrinp fed low dietary FM. Endoplasmic reticulum (ER) stress related genes expression in hepatopancreas were down-regulated and in intestine were upregulated by low dietary FM. Inhibitor kappa B kinase β expression in intestine increased with the dietary FM levels, while Dorsal expression in hepatopancreas showed the oppsite tendency. Hematoxylin and eosin (H&E) stain and transmission electron microscope analysis of intestinal samples indicated that low FM diets induced intestinal morphological damage, ER swollen and chromatin condensation. UPLC-Q/TOF-MS analysis indicated that degree of unsaturation of the fatty acid chains of phospholipids in hemolymph decreased with the decreasing dietary FM levels. Lysophospholipids and bile acids metabolism were disturbed by high levels of FM sparing in diet. These results indicated when dietary FM contents decreased, ER stress of shrimp was induced. The decreased unsaturated degree of phospholipids, decreased contents of lysophospholipids, altered lipid metabolism and ER stress may responsible for the impaired growth performance and health of shrimp fed a low FM diets.